Community Social Psychology dimensions facing ethnic and racial issues - Jefferson Olivatto Da Silva (Semina: Ciências Sociais e Humanas, 2017)
Ethnic and racial issues lead to new forms to the Brazilian psychological praxis. Psychological suffering from racists’ relations resulted from psychosocial dynamics of long-term. On the opposite, social behavior of black people overcomes that by perpetuating meaningful and symbolical process through the whole Colonial and Republic Brazilian lifespan. We will demonstrate that psychological contingency can help to understand psychosocial process related to a long-term period. Maritza Montero’s psychological dimensions and Social Sciences interface will explain contingency approach. Thus, we conclude that psychological dimensions show a new way of observing social behavior of Brazilian black people, whom promoted identity links in daily relationships, through collective and affectional recognition, whereas social asymmetry perpetuated itself in Brazilian Social History.